Nano-Pd/Chitosan Composite: An Extremely Effective Catalyst to the Synthesis of Pyrazolyl Analogues through Suzuki–Miyaura Cross-Coupling Reactions in an Aqueous Medium - M. Senthilkumar; P. Manisankar; R. Pandimurugan; P. A. Vivekanand; Govindasami Periyasami; S. Harikumar; Perumal Karthikeyan; Mostafizur Rahaman; Santosh Khanal (Journal of Chemistry)
Substituted pyrazolyl derivatives were synthesized through Suzuki cross coupling of aromatic boronic acid with heterocyclic halide using newly synthesized nano-Pd/chitosan catalyst by the water-mediated green synthesis methodology. The reactivity of the nano-Pd catalyst was highly enhanced by incorporating palladium nanoparticles with a biopolymer chitosan matrix. The synthesized nano-Pd/chitosan catalyst was studied thoroughly for its structure, morphology, and other fundamental aspects such as the size and shape by various techniques including XRD, FESEM, and EDAX analyses. The scope of the catalyst was disclosed by their great stability with remarkable reusability for Suzuki cross-coupling reaction with twelve different boronic acids under the green synthetic methodology.